Pemanfaatan Media Pembelajaran dalam Pembelajaran Tematik Terpadu di Sekolah Dasar - Helmalia, Evi; Dewi, Sri Enggar Kencana (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
This article explores the application of educational resources within the framework of integrated thematic learning at the primary school level. Integrated thematic learning is gaining popularity as an approach aimed at strengthening the interconnectedness between subjects and the practical relevance of learning. In this context, the incorporation of educational resources plays a pivotal role in enhancing students' learning experiences and deepening their comprehension of the subject matter. The article delineates various types of educational resources suitable for integrated thematic learning, along with effective strategies for seamlessly integrating these resources into the learning process. Furthermore, the article assesses the advantages of employing educational resources in boosting learning motivation, fostering student engagement, and improving overall learning outcomes. Thus, the article imparts valuable insights to educators regarding the significance of incorporating educational resources within the realm of integrated thematic learning in elementary schools.